1996
DOI: 10.1111/j.1550-7408.1996.tb05005.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Monoclonal Antibodies Define a Distinct, Conserved Epitope on an Apical Complex Exoantigen of Cryptosporidium parvum Sporozoites

Abstract: Development of optimal passive and active immunization strategies for cryptosporidiosis is dependent on the identification and characterization of functional parasite molecules which can be targeted. Each of a subset of five monoclonal antibodies (mAb) produced against immunoaffinity-isolated C. parvum antigens elicited distinct morphologic changes in sporozoites and merozoites, characterized by progressive formation and eventual release of membranous antigen-mAb precipitates from the sporozoite posterior m g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(94 citation statements)
references
References 10 publications
(5 reference statements)
3
91
0
Order By: Relevance
“…The propagation of C. parvum (Iowa isolate) in calves and oocyst purification [34][35][36][37], synthesis of BKIs [22,25,27,38], in vitro CpCDPK1 enzyme assay [22,25,38], in vitro determination of C. parvum BKI sensitivity [22,25,38,39], neonatal mouse [36,40] and calf models of C. parvum infection [37,[41][42][43], and pharmacologic measurement of BKI plasma and stool levels and plasma protein binding have all been previously described [27,44]. BKI-1294 and BKI-1553 were synthesized on the pyrazolo [2,3-d] pyrimidine scaffold, while BKI-1517 was synthesized on a 5-aminopyrazole-4-carboxamide scaffold [25] (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The propagation of C. parvum (Iowa isolate) in calves and oocyst purification [34][35][36][37], synthesis of BKIs [22,25,27,38], in vitro CpCDPK1 enzyme assay [22,25,38], in vitro determination of C. parvum BKI sensitivity [22,25,38,39], neonatal mouse [36,40] and calf models of C. parvum infection [37,[41][42][43], and pharmacologic measurement of BKI plasma and stool levels and plasma protein binding have all been previously described [27,44]. BKI-1294 and BKI-1553 were synthesized on the pyrazolo [2,3-d] pyrimidine scaffold, while BKI-1517 was synthesized on a 5-aminopyrazole-4-carboxamide scaffold [25] (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a panel of second-generation MAbs was produced against immunoaffinity-purified GP25-200 (39) and P23 (42) to determine whether the antigens contain additional neutralizationsensitive epitopes that could be targeted to enhance efficacy. We recently reported that one of the resulting MAbs produced from GP25-200-immunized mice, designated 3E2, elicited the circumsporozoite precipitate (CSP)-like reaction (36,39). This reaction, named after the malarial CSP reaction (7), is characterized by the progressive posterior formation and release of membranous antigen-MAb complexes, after which zoites are rendered noninfective (36,39).…”
mentioning
confidence: 99%
“…Therefore, effective neutralization of the infective stages could prevent initiation of the life cycle or interrupt and terminate the cycle in an existing infection. The C. parvum antigens GP25-200 (1,39), CSL (39,40), and P23 (1,23) were selected as targets for the present study. Each antigen is involved in the pathogenesis of infection, expressed on the surface of both infective zoite stages, and conserved on diverse C. parvum isolates (1,23,31,39,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins, as well as proteins on the surface of the zoite, facilitate attachment to the cell surface, gliding motility, and subsequent invasion and intracellular development of the parasite. However, unlike those of other apicomplexans, most of the Cryptosporidium surface and apical complex antigens that have been characterized are glycoproteins [9][10][11][12][13][14]. Two of these, gp900 [10] and gp40/15 [11,13,14], are mucin-like glycoproteins, proteins with high percentages of serine and threonine residues that are sites for O-linked glycosylation.…”
Section: Introductionmentioning
confidence: 99%